THE USE OF GOOGLE SITES FOR TEACHERS AND ADMINISTRATIVE PERSONNEL AS AN EFFORT FOR STUDENT DATA MANAGEMENT EFFICIENCY AT SMPN 19 SURABAYA & SMPN 52 SURABAYA - Ghani, Mohammad; Fakhruzzaman, Muhammad Noor; Maryamah; Susanto, Putri Dwidhamayanti; Basuki, Lintang Sabrang Kinasih (Universitas Airlangga, 2024)
Utilization of student data can help teachers and school administration staff for management efficiency. This community service program in the form of Google Sites training seeks to help improve the skills and knowledge of teachers and administration staff. This community service program is inseparable from the SDG's elements as the basic foundation for program implementation, namely: Quality Education (4th indicator), and Industry, Innovation, and Infrastructure (9th indicator). This aims to increase the skills and knowledge of teachers and administration staff and ultimately encourage innovation in creating student data management that can support school infrastructure. The method used as an effort to improve skills is by providing training as well as pre-tests and post-tests for participants. Based on statistical tests, there is a significant difference between the Pre-Test and Post-Test values, namely with an average value of 7.5 (Pre-Test) and 8.2 (Post-Test). Based on the Wilcoxon sign rank test, it also shows that there is a difference between the Pre-Test and Post-Test values ​​with a Wcount value <Wtable.